The Growth of Higher Educators for Social Justice: Collaborative Professional Development in Higher Education - Molly K. Ness; Marshall A. George; Kristen Hawley Turner; Jane Bolgatz (Park University, 2010)
In this article, we investigate what happened when, contrary to the typical isolation of faculty in higher education, a group of higher educators from various disciplines in a graduate school of education met regularly to discuss issues related to our teaching and social justice. More specifically, we explored the following research question: How does collaboration among higher educators from various disciplines shape their beliefs and practices of teaching for social justice? Over three years of collaboration and conversation, not only did we expand our own knowledge and understandings of notions of social justice, but we began to take important steps towards increasing our social justice actions in our teaching. This article explores our efforts to create a self-directed professional development group of higher educators and provides suggestions for similarly interested higher educators.